2023
DOI: 10.1515/htmp-2022-0265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tool traverse speed on joint line remnant and mechanical properties of friction stir welded 2195-T8 Al–Li alloy joints

Abstract: AA2195-T8 Al–Li alloy plates were welded by friction stir welding (FSW) at tool rotational speed of 1,000 rpm and tool traverse speeds (TS) of 100–400 mm·min−1 under three types of butting surface conditions, i.e., (1) without butting surface treatment, (2) butting surface milled, and (3) bead-on-plate welding. The effect of welding heat input and butting surface condition on joint line remnant (JLR) and mechanical properties of friction stir welded 2195-T8 Al–Li alloy was investigated comprehensively. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The abnormal fracture phenomenon is more prevalent in the FSW Al-Li alloy joints with thin plates, which is attributed to the strong action from the tool shoulder. Yan et al [8] obtained defect-free joints in 2195-T8 alloy plates with 2 mm thickness, but the joints were fractured at the NZs during tensile tests, and similar results can also be found in some FSW joints of Al-Li alloys with medium thickness [12,14]. Chen et al [21] speculated that the abnormal fracture was related to the 'S' line originating from the fragmented oxide film at the plate butt surface.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The abnormal fracture phenomenon is more prevalent in the FSW Al-Li alloy joints with thin plates, which is attributed to the strong action from the tool shoulder. Yan et al [8] obtained defect-free joints in 2195-T8 alloy plates with 2 mm thickness, but the joints were fractured at the NZs during tensile tests, and similar results can also be found in some FSW joints of Al-Li alloys with medium thickness [12,14]. Chen et al [21] speculated that the abnormal fracture was related to the 'S' line originating from the fragmented oxide film at the plate butt surface.…”
Section: Introductionmentioning
confidence: 89%
“…It is clear that obtaining a defect-free FSW joint of Al-Li alloy with medium thickness is very challenging. Figure 2 summarises the welding performances of the present FSW joints and reported sound joints of 2195 and 2198 alloys with medium thickness [10][11][12][13][14][15][16][17][18], which shows a narrow zone under a blue dotted line for the sound FSW joints. It is concluded that the welding speeds of most sound joints were usually lower than 300 mm/min, and a relatively high welding speed of 400 mm/min (actually a moderate welding speed) can be accepted only at a moderate tool rotational speed of 800 rpm.…”
Section: Weld Formingmentioning
confidence: 94%
See 3 more Smart Citations